2014
DOI: 10.1111/ssm.12047
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improving the Mathematics Preparation of Elementary Preservice Teachers

Abstract: Research suggests the importance of mathematics knowledge for teaching (MKT) for enabling elementary school teachers to effectively teach mathematics. MKT involves both mathematical content knowledge (M‐CK) and mathematical pedagogical content knowledge (M‐PCK). However, there is no consensus on how best to prepare elementary preservice teachers (PSTs) to achieve M‐CK and M‐PCK. This study builds on research related to MKT by investigating influences of mathematics content courses designed specifically for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Similarly, Burton (2012), who researched the ability of certain content methods courses to change PSTs' attitudes toward mathematics, suggested that qualitative data could provide valuable information on different factors that influence the change process that occurs in PSTs. Cardetti and Truxaw (2014) and Dreher et al (2016) presented suggestions in line with the previously outlined, asserting that qualitative data would provide details that quantitative data fails to capture.…”
Section: Methodsmentioning
confidence: 63%
See 3 more Smart Citations
“…Similarly, Burton (2012), who researched the ability of certain content methods courses to change PSTs' attitudes toward mathematics, suggested that qualitative data could provide valuable information on different factors that influence the change process that occurs in PSTs. Cardetti and Truxaw (2014) and Dreher et al (2016) presented suggestions in line with the previously outlined, asserting that qualitative data would provide details that quantitative data fails to capture.…”
Section: Methodsmentioning
confidence: 63%
“…A number of researchers indicate a need for future research to include more qualitative data relative to PSTs' experiences, expectations, beliefs, and attitudes toward mathematics (Briley, 2012;Burton, 2012;Cardetti & Truxaw, 2014;& Dreher et al, 2016). Briley (2012) posited that qualitative data could add richness and clues to complexities of our current understanding of the relationships between mathematics teaching efficacy, mathematics self-efficacy, and mathematical beliefs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers' confidence in teaching mathematics has been shown to be significantly associated with their students' confidence in learning mathematics (Mata et al, 2012;Mensah et al, 2013;Stipek et al, 2001). Research has also emphasized the importance of a specific "teaching mathematics knowledge" to increase teacher confidence and teaching effectiveness (Ball, 2000;Cardetti & Truxaw, 2014). One study focused on female elementary teachers and their levels of mathematics anxiety found the negative impact of the teachers' anxiety toward mathematics transferred to their female students but not their male students (Beilock, 2009).…”
Section: Teachers' Impact On Student Mathematics Anxietymentioning
confidence: 99%